2008
DOI: 10.1007/s11244-008-9088-x
|View full text |Cite
|
Sign up to set email alerts
|

A Bentonitic Clay Assisted Method for the Preparation of 2-(R-Anilino)-1, 4-Naphthoquinones

Abstract: A new and efficient protocol to prepare 2-(R-anilino)-1,4-naphthoquinones in quantitative yields is presented. This synthesis occurs under mild conditions by reacting the corresponding aniline and 1,4-naphthoquinone in the presence of a bentonitic clay. The role of the clay is explained in terms of a reaction mechanism in which an activated complex is formed by the reaction of 1,4-naphthoquinone with Lewis acid sites of the clay. Based on the chemical composition of the clay, with Fe 3+ sites, the last step of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…The presence of a Lewis acid and oxidant species Fe +3 in the clay was clearly important. 34 In a subsequent study, we reported the preparation of novel Nucleophilic aryl amines react rather easily with 2,3-dichloro-1,4-naphthoquinone 2, replacing one chlorine atom to give 2-anilino-3-chloro-1,4-naphthoquinone 3. However, the electronically enriched quinone 3 is rendered less reactive to nucleophiles and further substitution of second chlorine is inhibited.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a Lewis acid and oxidant species Fe +3 in the clay was clearly important. 34 In a subsequent study, we reported the preparation of novel Nucleophilic aryl amines react rather easily with 2,3-dichloro-1,4-naphthoquinone 2, replacing one chlorine atom to give 2-anilino-3-chloro-1,4-naphthoquinone 3. However, the electronically enriched quinone 3 is rendered less reactive to nucleophiles and further substitution of second chlorine is inhibited.…”
Section: Methodsmentioning
confidence: 99%
“…33 The catalytic effect of Lewis acids in the reaction of anilines with 1,4-naphthoquinone has been previously documented by us. 34 We reported a bentonitic clay-assisted preparation of 2-chloroanilino-1,4-naphthoquinones. The presence of a Lewis acid and oxidant species Fe +3 in the clay was clearly important.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported a bentonitic clay assisted preparation of 2-(chloroanilino)-1,4-naphthoquinones [28]. However, to the best of our knowledge there are no reports on the optimal conditions to prepare 2-(fluoroanilino)-1,4-naphthoquinones.…”
Section: Synthesis and Reaction Pathwaymentioning
confidence: 99%
“…20 The use of a bentonitic clay and ultrasonic irradiation were reported to give moderate to excellent yields of 2-amino-1,4-naphthoquinones. 21 With the objective of studying concise routes into natural products, their analogues, and polyheteroaromatic systems with the 2-amino-1,4-naphthoquinone moiety, we initially investigated a synthetic protocol. To the best of our knowledge, an efficient synthesis of 2-amino-1,4-naphthoquinones via a t-BuOK mediated direct amination has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“… 20 The use of a bentonitic clay and ultrasonic irradiation were reported to give moderate to excellent yields of 2-amino-1,4-naphthoquinones. 21 …”
Section: Introductionmentioning
confidence: 99%